1994
DOI: 10.1051/apido:19940206
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the size of eggs from Apis mellifera L queens and laying workers

Abstract: Summary — The shortest eggs laid by A m mellifera laying workers were shorter, and the longest were longer than eggs deposited by queens. The coefficient of variance for length of eggs deposited by laying workers was 3.5 times higher than for eggs from queens. Eggs from queens were longer (1.620 mm), but narrower (0.368 mm) than eggs from laying workers (1.579 and 0.378 mm). Correlation coefficient between length and width was significant for eggs from laying workers but not from queens. Both types of A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Few studies have addressed the evolutionary and ecological implications of egg size in social insects (Matsuura & Kobayashi, 2010;Villet, 1990), and our understanding of egg size variation in social insects, including the western honey Bee (Apis mellifera L.), is very limited. Some descriptive studies in honey bees exist, reporting variation between male and female eggs (Wegener, Lorenz, & Bienefeld, 2010;Woyke, 1994), across maternal ages (Al-Lawati & Bienefeld, 2009), castes (even though these differences might be functionally significant as well: Gençer & Woyke, 2006) and among seasons (Henderson, 1992). It was found that eggs from queens are longer but narrower compared to eggs from laying workers in the western honey bee (Woyke, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have addressed the evolutionary and ecological implications of egg size in social insects (Matsuura & Kobayashi, 2010;Villet, 1990), and our understanding of egg size variation in social insects, including the western honey Bee (Apis mellifera L.), is very limited. Some descriptive studies in honey bees exist, reporting variation between male and female eggs (Wegener, Lorenz, & Bienefeld, 2010;Woyke, 1994), across maternal ages (Al-Lawati & Bienefeld, 2009), castes (even though these differences might be functionally significant as well: Gençer & Woyke, 2006) and among seasons (Henderson, 1992). It was found that eggs from queens are longer but narrower compared to eggs from laying workers in the western honey bee (Woyke, 1994).…”
mentioning
confidence: 99%
“…Some descriptive studies in honey bees exist, reporting variation between male and female eggs (Wegener, Lorenz, & Bienefeld, 2010;Woyke, 1994), across maternal ages (Al-Lawati & Bienefeld, 2009), castes (even though these differences might be functionally significant as well: Gençer & Woyke, 2006) and among seasons (Henderson, 1992). It was found that eggs from queens are longer but narrower compared to eggs from laying workers in the western honey bee (Woyke, 1994). However, further experiments indicated that worker-laid eggs are longer, wider with larger volume and heavier than queen-laid eggs (Gençer & Woyke, 2006;Wegener et al, 2010).…”
mentioning
confidence: 99%
“…In honeybees, egg size varies due to several factors: between castes, i.e. queen and workers (Woyke & Wongsiri, 1992;Woyke, 1994;Gençer & Woyke, 2006); according to seasons (Henderson, 1992); and due to changes in the metabolic process (Woyke, 1998). In stingless bees, eggs differ in size according to the species (Velthuis & Sommeijer, 1991), but there is little information on intra-specific variation.…”
Section: Introductionmentioning
confidence: 99%
“…In honeybees, egg size varies due to several factors: between castes, i.e. queen and workers (Woyke & Wongsiri, 1992;Woyke, 1994;Gençer & Woyke, 2006); according to seasons (Henderson, 1992); and due to changes in the metabolic process (Woyke, 1998). In stingless bees, eggs differ in size according to the species (Velthuis & Sommeijer, 1991), but there is little information on intra-specific variation.…”
Section: Introductionmentioning
confidence: 99%